2021
DOI: 10.3390/jcm10051014
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Response and Non-Reproducible Elevated Concentrations with a High-Sensitivity Cardiac Troponin I Assay

Abstract: High-sensitivity cardiac troponin (hs-cTn) testing has enabled physicians to make earlier diagnostic and prognostic decisions in the hospital setting than previous cardiac troponin assays. Analytical improvements have permitted one to measure cardiac troponin precisely in the nanogram per litre (ng/L) range with hs-cTn assays which has resulted in fast 0/1-h and 0/2-h algorithms for ruling-in and ruling-out myocardial infarction. Although analytical interferences that affect the reporting of hs-cTn are uncommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The findings from both studies reported here support recent clinical data indicating that the OCD hs-cTnI may misclassify biochemical injury in approximately 10% of the population being evaluated for myocardial injury [14][15][16]. Despite OCD using the same three antibodies in their cTnI ES (contemporary/conventional) assay and their hs-cTnI (high-sensitivity) assay [22], there is better agreement between the cTnI ES assay with the Abbott hs-cTnI assay as compared to the OCD hs-cTnI assay.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The findings from both studies reported here support recent clinical data indicating that the OCD hs-cTnI may misclassify biochemical injury in approximately 10% of the population being evaluated for myocardial injury [14][15][16]. Despite OCD using the same three antibodies in their cTnI ES (contemporary/conventional) assay and their hs-cTnI (high-sensitivity) assay [22], there is better agreement between the cTnI ES assay with the Abbott hs-cTnI assay as compared to the OCD hs-cTnI assay.…”
Section: Discussionsupporting
confidence: 87%
“…There were 469 samples (HGH = 137, JHCC = 150, SJH = 118, WLMH = 39, MUMC = 25) with sufficient volume for testing in the following order: Abbott ARCHITECT (Abbott Laboratories, Chicago, IL, USA) hs-cTnI, OCD (Ortho Clinical Diagnostics, Raritan, NJ, USA) VITROS XT 7600 hs-cTnI, OCD VITROS XT 7600 cTnI ES (run 1); then immediately retested in the following order except for cTnI ES (cTnI ES is OCD's contemporary/conventional assay and in run 2 only hs-cTnI was measured to maximize the number of samples for duplicate measurements for the hs-cTnI assays n = 411). Acceptable repeats were identified if the difference between results was ≤3 ng/L for average concentrations <15 ng/L or ≤20% for concentrations ≥15 ng/L, consistent with previous analyses [12,16]. The mean, coefficient of variations (CVs), and number of measurements for the QC for the assays during the testing were as follows: OCD cTnI ES: level 1 mean = 0.076 µg/L/CV = 3.6%/n = 8; level 2 mean = 0.654 µg/L/CV = 2.5%/n = 8; level 3 mean = 7.168 µg/L/CV = 1.9%/n = 8 | OCD hs-cTnI: level 1 mean = 6.3 ng/L/CV = 13.7%/n = 25; level 2 mean = 36.5 ng/L/CV = 11.8%/n = 27; level 3 mean = 8120.9 ng/L/CV = 7.5%/n = 27 | Abbott hs-cTnI level 1 mean = 12.4 ng/L/CV = 4.1%/n = 9; level 2 mean = 49.2 ng/L/CV = 4.7%/n = 9; level 3 mean = 14,094.4 ng/L/CV = 12.9%/n = 12.…”
Section: Studysupporting
confidence: 70%
See 3 more Smart Citations